Pyoderma gangrenosum: problems related to the diagnostics and treatment - A. V. Patrushev; A. V. Samtsov; V. V. Barbinov; A. V. Sukharev; I. E. Belousova (Vestnik Dermatologii i Venerologii, 2017)
The authors provide current data related to the etiology, pathogenesis, classification, clinical picture, differential diagnostics and treatment methods of pyoderma gangrenosum.